Research on nondestructive identification and location algorithm of cables with discontinuous conductor diameters based on broadband impedance spectrum - Zhixiang Deng; Shuai Wang; Haibao Mu; Daning Zhang; Guanjun Zhang; Jianbing Pan; Zaide Xu (Energy Reports, 2023)
The number of cables in the distribution system is extremely huge, but there are some cables with thinner conductors in the middle section, which may threaten the safety of the system. At present, there is no effective detection method for such problems. Based on the broadband impedance spectrum, this paper proposes an algorithm to identify and locate the cables with discontinuous conductor diameters in the middle using the integral transformation with Chebyshev window. The simulation and experimental results show that the algorithm proposed in this paper can realize the identification and location of the conductor thinning cable in the middle section, and the location error is less than 0.76%.